Biased Use of the IGHV4 Family and Evidence for Antigen Selection in Chlamydophila psittaci-Negative Ocular Adnexal Extranodal Marginal Zone Lymphomas - Zhu, Daxing; Lossos, Chen; Chapman-Fredricks, Jennifer R.; Matthews, Julie M.; Ikpatt, Offiong F.; Ruiz, Phillip; Lossos, Izidore S. (PloS one, 2011)
Extranodal marginal zone lymphomas (EMZL) are the most common lymphomas in the ocular adnexa. The etiology and potential role for antigenic stimulation in these lymphomas are still controversial. We have examined IGHV gene usage and mutations in 67 Chlamydophila psittaci-negative ocular adnexal EMZL. Clonal IGHV gene sequences were identified in 43 tumors originating from the orbit (19), conjunctivae (18) and lacrimal gland (6). Forty four potentially functional clonal IGHV gene sequences were detected with overrepresentation of the IGHV4 family and IGHV4-34 gene. All but 3 sequences were mutated with the average percent homology to the germ line of 93.5±6.1. Multinomial model and Focused binomial test demonstrated evidence for positive and/or negative antigen selection in 59% of the potentially functional IGHV genes. Intraclonal variation was detected in 8 of 11 tumor specimens. Overall our findings demonstrate that C. psittaci-negative ocular adnexal EMZL exhibit biased usage of IGHV families and genes with evidence for intraclonal heterogeneity and antigen selection in multiple tumors, implicating B-cell receptor-mediated antigen stimulation in the pathogenesis of these lymphomas.